Application of CD56, P63 and CK19 immunohistochemistry in the diagnosis of papillary carcinoma of the thyroid - Alowami Salem; Nasr Ahmed; El Demellawy Dina (BMC, 2008)
Abstract Papillary carcinoma of the thyroid (PTC) is the commonest thyroid cancer. In the recent decades an obvious increase in the incidence of PTC has occurred. The pathological diagnosis of PTC is usually an easy diagnosis in the majority of cases. However since the introduction of follicular variant of PTC and the wide threshold range in interpretation of the clearly set pathological criteria for diagnosis of PTC, between pathologists including experts, the diagnosis in some cases became quite difficult. Unfortunately some cases are unjustifiably over-called as follicular variant of PTC as a result of the wide inter observable variability between pathologists, including thyroid pathologists. Ancillary studies such as immmunohistochemistry may be helpful, but till now there is no 100% consistent marker(s), that distinct between PTC and other follicular thyroid lesions and tumors. We assessed expression of antibodies against CD56, CK19, P63 and E-Cadherin in PTC and other follicular thyroid lesions and neoplasms. A total of 175 cases were studied. The neoplastic cases included 75 carcinomas (72 papillary, 2 follicular, 1 Hurthle cell) and 35 adenomas (32 follicular and 3 Hurthle cell). The non-neoplastic thyroids included 65 cases, (25 nodular hyperplasia, 5 thyrotoxic hyperplasia (Grave's disease), 19 lymphocytic thyroiditis and 6 Hashimoto's thyroiditis). All cases were evaluated by immunohistochemistry for the expression of the above mentioned markers. The markers' patterns and intensities of staining were scored. Positive expression of the markers equal or >10% of the follicular epithelium within the tumor or lesional cells was considered positive. An expression of <10% was considered to be negative. Our results showed CD56 positive in all the lesions and tumors except for PTC in all cases (100%). CD56 was negative in all PTC cases (100%). CK 19 showed positive expression in PTC accounting for 85% of cases and in 26% of non PTC lesions/tumors. P63 showed selective focal positivity in PTC cases, in contrast to other non PTC lesions/tumors. P63 expression was in 70% of cases of PTC and was consistently absent in all the non PTC cases. E-Cadherin showed consistent non discriminatory expression in all cases included in the study. We concluded that a panel consisted of CD56, CK19 and P63 is of value in distinction of PTC from other thyroid follicular lesion. P63 is a specific but less sensitive marker for PTC than CK19. CD56 is more specific and sensitive marker than CK19, however it is a negative rather than a positive marker for PTC. E-Cadherin is of no value in the diagnosis of thyroid follicular lesions/tumors. We recommend application of a panel composed of CK19, P63 and CD56 by a group of expert thyroid pathologists on a large series of follicular malignant thyroid neoplasms of uncertain malignant.